2013
DOI: 10.1037/a0031956
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific differential prediction of college admission tests: A meta-analysis.

Abstract: This is the first meta-analysis that investigates the differential prediction of undergraduate and graduate college admission tests for women and men. Findings on 130 independent samples representing 493,048 students are summarized. The underprediction of women's academic performance (d ϭ 0.14) and the overprediction of men's academic performance (d ϭ -0.16) are generalizable, albeit small. Transferred onto a 4-point grading scale, women earn college grades that are 0.24 points higher than those of men with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 70 publications
5
32
0
6
Order By: Relevance
“…The Swedish research has had a strong focus on predictive validity, and the results show that the grades are better predictors than the test (see Lyrén, 2008;Wolming and Wikström, 2010, for overviews). These findings are consistent with international observations that academic performance is more strongly correlated with school grades than with admissions' test scores (see, for instance, Linn, 1990;Zwick, 2002;Fischer et al, 2013b). The difference in predictive power between the grades and tests may be due to differences in what the instruments measure.…”
Section: Previous Researchsupporting
confidence: 80%
See 1 more Smart Citation
“…The Swedish research has had a strong focus on predictive validity, and the results show that the grades are better predictors than the test (see Lyrén, 2008;Wolming and Wikström, 2010, for overviews). These findings are consistent with international observations that academic performance is more strongly correlated with school grades than with admissions' test scores (see, for instance, Linn, 1990;Zwick, 2002;Fischer et al, 2013b). The difference in predictive power between the grades and tests may be due to differences in what the instruments measure.…”
Section: Previous Researchsupporting
confidence: 80%
“…For example, Fischer et al (2013b) found that female students' college performance is under-predicted by SAT scores, while male students' performance is over-predicted. It is well known that SES also affects academic achievement in general, although Delaney et al (2011) show that this effect diminishes during higher education, and that SES has stronger effects for male students than for female students.…”
Section: Previous Researchmentioning
confidence: 99%
“…Because the participants in this study received a description of a situation in which the only difference was students' gender (female or male name), the results withdraw attention for the potential involuntary activation of gender stereotypes or social representations of gender, which are characterized by girls' behaving better and presenting better results at school (Auwarter & Aruguete, 2008;Carvalho, 2016;Fischer, Schult, & Hell, 2013;Robinson & Lubienski, 2011). Although these differences in estimates do not necessary lead to a discriminatory approach to male students, this effect should be taken into consideration, because it may create the conditions for potentially differentiating actions by teachers, such as providing different opportunities, distinct feedback styles, patterns of interaction, and reinforcement, depending on the student.…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analysis of gender differences in teacher-assigned grades demonstrated a small but significant female advantage (Fischer et al 2013;Richardson et al 2012;Voyer and Voyer 2014). Many studies showed that throughout elementary, middle and high school, girls achieved higher grades than boys in all major subjects, even though their scores were lower or equal in tests, especially maths and science (for research reviews, see Duckworth and Seligman 2006;Ekstrom 1994;Kling et al 2013).…”
Section: Gender Gap In School Gradesmentioning
confidence: 99%